The Mediating Role of Burnout in the Effect of Job Stress on Turnover Intention Among Paramedics at Puri Raharja General Hospital - Ni Kadek Meriyanti; I Gede Riana (International Journal of Economics, Management and Accounting, 2025)
This study aims to analyze the mediating role of burnout in the effect of job stress on the turnover intention of paramedics at Puri Raharja General Hospital. A saturated sampling technique was used, involving all 80 employees as the sample. The research applied a survey method using questionnaires and interviews, analyzed with descriptive statistics and inferential statistics using Partial Least Squares (PLS). The results showed that job stress has a positive and significant effect on turnover intention. Job stress also has a positive and significant effect on burnout. Furthermore, burnout positively and significantly affects turnover intention and partially mediates the relationship between job stress and turnover intention.